الرضى الوظيفي لدى مستشاري التوجيه والارشاد المدرسي والمهني دراسة ميدانية لمستشاري التوجيه للمتوسط والثانوي – ولاية الوادي - - قديري, عبد الوهاب (University of Eloued جامعة الوادي, 2023)
يتضمن هذا البحث الموسوم بـ: الرضى الوظيفي لدى مستشاري التوجيه والارشاد المدرسي والمهني -دراسة ميدانية لمستشاري التوجيه للمتوسط والثانوي – ولاية الوادي –" الكشف على مستوى الرضا الوظيفي لدى مستشاري التوجيه والإرشاد المدرسي والمهني لولاية الوادي، وذلك تبعا لثلاثة متغيرات مهمة، وهي: الجنس، والخبرة المهنية، والتخصص، وقد جسدنا هذا العمل عبر إعداد استبيان الرضا الوظيفي على عينة مؤلفة من حوالي 60 مستشارا ومستشارة للتوجيه والإرشاد المدرسي والمهني ، وقد كانت النتائج المتحصل عليها على النحو الآتي:  ان مستشار التوجيه والإرشاد المدرسي والمهني يتمتع بمستوى عالي من الرضا الوظيفي.  أنه لا توجد فروق ذات دلالة إحصائية في درجة الرضا الوظيفي لدى مستشار التوجيه والإرشاد المدرسي والمهني تعزى لمتغير الجنس  لا توجد فروق ذات دلالة إحصائية في درجة الرضا الوظيفي لدى مستشار التوجيه والإرشاد المدرسي والمهني تعزى لمتغير الخبرة المهنية  توجد فروق ذات دلالة إحصائية في درجة الرضا الوظيفي لدى مستشار التوجيه والإرشاد المدرسي والمهني تعزى لمتغير التخصص الكلمات المفتاحية: الرضا الوظيفي؛ مستشار التوجيه والإرشاد المدرسي والمهني؛ المتوسط والثانوي ؛ ولاية الوادي. Abstracts This research includes: Job satisfaction among school and vocational guidance and counseling counselors - A field study of guidance counselors for intermediate and secondary schools - El-Wadi state - "Disclosure of the level of job satisfaction among school and vocational guidance and counseling counselors in El-Wadi state, according to three important variables: gender, And professional experience, and specialization, and we embodied this work by preparing a job satisfaction questionnaire on a sample consisting of about 60 male and female counselors for school and vocational guidance and counseling, and the results obtained were as follows:  There are no statistically significant differences in the degree of job satisfaction of the school and vocational guidance and counseling counselor due to the gender variable.  There are no statistically significant differences in the degree of job satisfaction of the school and vocational guidance and counseling counselor due to the variable of professional experience.  There are statistically significant differences in the degree of job satisfaction of the school and vocational guidance and counseling counselor due to the variable of specialization.
تخصص علم نفس